تطبيق استراتيجيّة التّعليم (فكر- زاوج- شارك) في تعليم مادّة اللغة العربيّة في المدرسة الثّانويّة الإسلاميّة الحكوميّة ٤ آغام - Fitrah, Yulinus; Yusra, Oktarina; Nurhasnah, Nurhasnah; Febrianta, Rita (Darul Yasin Al Sys, 2023)
The problems of this research are the researcher notes when the teacher applies the education strategy (Think-Pair-Participate) in teaching the Arabic language subject in the Islamic State Secondary School 4 Agam. Which students possess, until he found difficulties in learning discussion. As for the objectives of this research, to find out the application of the education strategy (Think, Pair, Share) in teaching the Arabic language in the tenth semester of the Department of Natural Sciences at the Governmental Islamic Secondary School 4 Agam. In this research, the researcher used field research, that is, data collection takes place directly at the research site. This research is descriptive. The research community is the students of the tenth semester of the Department of Natural Sciences. Data analysis method: observation, interview, and documentation. The researcher found that a female teacher applied the education strategy (Think-Pair-Participate) in teaching the Arabic language in the tenth semester of the Department of Natural Sciences at the Governmental Islamic Secondary School 4 Agam well. But the discussion between pairs is still not ideal, because the discussions that should focus on the students are in fact centered on the teacher.